1999
DOI: 10.1159/000012791
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits in the German EPIC Cohorts: Food Group Intake Estimated with the Food Frequency Questionnaire

Abstract: In the baseline assessment of the two EPIC-Germany cohorts Heidelberg and Potsdam, dietary information was obtained with an identical food frequency questionnaire (FFQ). The optically readable FFQ was designed to assess the usual food and nutrient intake of individuals during the past 12 months. The present analysis was based on dietary data from 25,212 participants in Heidelberg (11,776 men, 13,436 women) and 26,270 participants in Potsdam (10,249 men, 16,021 women). This paper presents the first results of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…In Heidelberg, this was the case for only 62%, and 37% of recalls were obtained at home. The differences observed between the Heidelberg and Potsdam cohorts agree well with findings from the FFQ applied as the basic dietary assessment tool in EPIC-Germany [9]. The exposure variation was increased by having two instead of one EPIC study centers in Germany.…”
supporting
confidence: 80%
“…In Heidelberg, this was the case for only 62%, and 37% of recalls were obtained at home. The differences observed between the Heidelberg and Potsdam cohorts agree well with findings from the FFQ applied as the basic dietary assessment tool in EPIC-Germany [9]. The exposure variation was increased by having two instead of one EPIC study centers in Germany.…”
supporting
confidence: 80%
“…Among 497 controls contacted, 435 were eligible, and 300 (69.0%) participated. Hospital controls were selected from patients consecutively hospitalized at the neurology Nutritional factors (meat, sugar, vitamin C, vitamin E, beta-carotene), 15 mother's profession, availability of fixed hot water during childhood, 16 and body mass index were not different between groups (PϾ0.1; data not shown). Probability values are based on univariate logistic regression analysis stratified for sex and age.…”
Section: Methodsmentioning
confidence: 99%
“…Trained interviewers used a standardized questionnaire that focused on previous diseases and vascular and periodontal risk factors, including a detailed assessment of smoking and drinking habits, 14 nutrition, 15 childhood and adult social history, 16 past and present medication use, and dental care (eg, frequency and duration of tooth brushing, frequency of dentist visits, previous dental treatments). Risk factors-eg, hypertension and diabetes mellitus-were diagnosed if the patient reported that a physician had previously diagnosed the condition or if the patient was on treatment.…”
Section: Interview and Dental Examinationmentioning
confidence: 99%
“…Subjects who agreed to an appointment at the examination center received a letter 10 days prior to the examination which was also valid for free public transportation. In addition, this mailing contained the food frequency questionnaire [10], and a questionnaire covering other lifestyle aspects [9]. The questionnaires were completed at home and brought to the examination center.…”
Section: Recruitment Proceduresmentioning
confidence: 99%